The Role Of Specialized Children's Development Institutions For Children In Confence With The Law - Jamhari, Muhammad Ari; Hilman, Didi; Mustika, Desty Anggie (Universitas Ibn Khaldun Bogor, 2024)
Children who are sentenced to crime at the Special Child Development Institution (LPKA) have the right to receive coaching, mentoring, supervision, mentoring, education and training, as well as other rights in accordance with the provisions of statutory regulations, the provision of education, skills training, guidance and fulfillment of other rights in accordance with with the provisions of the laws and regulations by LPKA. The problems in this research are: (1) What is the role of Special Child Development Institutions in the Development Process for Criminal Children